2013
DOI: 10.1016/j.bjane.2012.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Nociceptive, Analgesic and Pathohistological Effects of Intrathecal Dexmedetomidine and Bupivacaine in Rats

Abstract: There were no apparent pathohistological changes at least 24 hours after the intrathecal administration of a single dose of dexmedetomidine 3 μg and 10 μg. Dexmedetomidine added to bupivacaine for spinal block improves analgesia and prolongs block duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In clinical research, no adverse neurological outcomes have been reported with intrathecal use of dexmedetomidine as an adjunct to local anesthetic. [32][33][34][35] Recently, many studies have demonstrated that intrathecal ropivacaine or bupivacaine-dexmedetomidine may increase the duration and efficacy of analgesia and decrease postoperative analgesic use, without notable adverse effects. 11,12,36) The use of dexmedetomidine as an adjuvant to bupivacaine for covering Cesarean delivery provided better intra-operative analgesia and did not affect Apgar scores or caused any noticeable side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical research, no adverse neurological outcomes have been reported with intrathecal use of dexmedetomidine as an adjunct to local anesthetic. [32][33][34][35] Recently, many studies have demonstrated that intrathecal ropivacaine or bupivacaine-dexmedetomidine may increase the duration and efficacy of analgesia and decrease postoperative analgesic use, without notable adverse effects. 11,12,36) The use of dexmedetomidine as an adjuvant to bupivacaine for covering Cesarean delivery provided better intra-operative analgesia and did not affect Apgar scores or caused any noticeable side effects.…”
Section: Discussionmentioning
confidence: 99%
“…13,28) The intrathecal doses of dexmedetomidine used in our study were based on previous human studies wherein no neurotoxic effects were documented at these doses. [25][26][27][33][34][35] A limitation of this study was that a doseresponse experiment was not performed to determine the optimal dose of dexmedetomidine required for optimal suppression of shivering, but without causing any significant side effects. In the present study, dexmedetomidine was used as an adjuvant to hyperbaric bupivacaine in a dose of 5 µg as this dosage is reported to be associated with prolonged duration of sensory and motor block without significant side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the block midpoint of these 2 assessments was used for the analysis. The median duration of the nerve block was 18 hours (95% confidence interval [CI], [18][19][20] in the dexmedetomidine group and 14 hours (95% CI, [14][15][16] in the ropivacaine group (P = 0.0001).…”
Section: Dexmedetomidine Enhanced Block Duration and Postoperative Anmentioning
confidence: 99%
“…Continuous administration of spinal clonidine in Wistar rats during 14 days failed to demonstrate neurotoxic damage. [30] Erddivanli and coworkers injected male SpragueDawley rats [31] with 3 µg and 10 µg of intrathecal dexmedetomidine added to bupivacaine; they found no apparent pathohistological changes 24 hours after a single injection. In male Kunming mice 1 to 3 µg of dexmedetomidine displayed a robust analgesia via a alpha2-receptor in a dose dependent manner and no significant pathological impacts on the spinal cord were noticed, with a potential protective effects of lidocaine induced neural cell damage.…”
Section: Safety Of Spinal Clonidinementioning
confidence: 99%